Peningkatan Kualitas Batubara Low Calorie Menggunakan Minyak Pelumas Bekas Melalui Proses Upgrading Brown Coal - Rizqia Zahara Putri; Fadhilah Fadhilah (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Coal is one of the important energy sources, in the form of dense and heterogeneous layers of organic sedimentary rocks. Because of this heterogeneous nature, coal has different qualities, even though the place is in one place. The level of temperature and pressure experienced in a coal deposit depositional environment is not the same, this is one of the causes of the different qualities of coal produced. The difference in the quality of coal is classified based on the ratio of water content, metter minerals, fixed carbon, and based on its calorific value. Coal mining results generally show different rankings, from highest to lowest. The highest level of coal can be utilized directly by consumers, but for low rank coal it must be improved through a certain process to suit consumer demand. Low rank coal, high in water content. This is in line with the low calorific value in coal. Problems caused by the high water content include: Low efficiency in combustion, triggering occurs spontaneous combustion and the high costs incurred at the time of transportation. Low rank coal upgrading technology aims to reduce the value of water content in coal.Keywords: Coal, Sources, Quality Coal, Upgrading, Cost.